Impact of Substance Abuse on Terrorist Activities in Borno South Senatorial District Borno State - Tanko Shawulu Paul; Sani Inusa Milala (Jurnal Restorasi : Hukum dan Politik, 2025)
This research is carried out to critically review the incidence of drug abuse among youth and impact on terrorism in Borno south senatorial district. To make this research reality, a questionnaire was administered to collect information, the information was collected from different places. The motive behind the research on the incidence of drugs abuse among youth stem from the belief that both male and female now engage more on drugs than before. This research also seeks to find out factors responsible for the causes of drugs abuse and impact on terrorism. The collected data through questionnaire were analyzed computed in percentages. And the following were seen as the major factors of drugs abuse among youth. Experimental curiosity, peer group influence, lack of parental supervision, personality problems due to socio-economic conditions, the need to work for long hours, availability of the drugs, and to resist withdrawal symptoms. the research recommend that, The parent or guidance should put more effort on train good moral behaviors to their members and increase good emotional support so that if they can easily noticed any abnormalities it could be addressed immediately especially females, Government should increase their effort on controlling the importation and exportation of illegal drugs and also those unregistered chemist that are selling illegal drugs and other drug without the medical prescription should arrest, prosecute, and penalized and other dealers should also severely punished, There is need for proper mobilization and enlightens females on the implication and consequences of such behaviors through seminar, mass media and schools, there is need for government to created job opportunities and empowerment programmed for the lower class and unemployed females to prevent them from staying idle. The research used both primary and secondary data. Differential theory was adopted.